Decoupled Acoustic and Visual Components in the Multimodal Signals of the Common Cuckoo (Cuculus canorus) - Esposito, Martina; Ceraulo, Maria; Tuliozi, Beniamino; Buscaino, Giuseppa; Mazzola, Salvatore; Sala, Luigi; Dal Zotto, Matteo; Campobello, Daniela (Frontiers in Ecology and Evolution, 2021)
Because of its parasitic habits, reproduction costs of the common cuckoo (Cuculus canorus) are mostly spent in pre-laying activities. Female costs are limited to searching host nests and laying eggs whereas males spend time in performing intense vocal displays, possibly with territorial purpose. This last aspect, together with a sexual plumage dimorphism, points to both intra- and inter-sexual selections operating within this species. One element triggering sexual selection is a differential fitness accrued by different phenotypes. Before analyzing possible sexual selection mechanisms operating in cuckoos, it is therefore necessary to verify whether there is a variability among male secondary characters by describing and quantifying them. Here we aimed to quantitatively characterize the main two potential candidates of sexual selection traits, i.e., calls and displays, shown by males at perches. During the 2019 breeding season, in a site within the Po Plain, we both audio and video recorded cuckoo males at five different perches. We analyzed acoustic variables as well as display sequences searching for potential correlations. We found a significant variation among calls that could be clustered into four vocal types. We also found that no visual displays were associated with vocal displays; cuckoo males were either vocal and motionless or soundless and active. We discuss our results under the perspective of the potential value of sexual selection in brood parasites and its role in its parasitic habit.